PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Wenas, Karina Pramaisella; Ikhram, M. Abdi Dzil (Jurnal Kewirausahaan dan Inovasi, 2023)
The purpose of this study is to identify the effects of work discipline and workplace environment on employee performance at the Road and Bridge Technical Unit of East Java Bina Marga Public Works Department in Kediri. This explanatory research focuses on explaining the relationship between variables, i.e. work discipline (X1), workplace environment (X2), and employee performance (Y). Using census sampling, all 79 members of the population were selected as the sample. The instruments were assessed using validity and reliability tests, and the hypotheses were tested using F-test, T-test, and coefficient of determination test. Further, the data was examined using classical assumption test consisting of normality, multicollinearity, and heteroscedasticity tests and was analyzed using multiple linear regression. All tests and analyses were performed in IBM SPSS 25. This study finds that work discipline positively affects employee performance, that workplace environment significantly influences employee performance, and that workplace discipline and workplace environment simultaneously influence employee performance.